Semi-analytical technique for isolating the pseudo-Rayleigh component of the field induced by a transiently responding submerged cylindrical shell. (August 2016) - Iakovlev, S.; Pyke, D.; Santos, H.A.F.A.
Abstract: A semi-analytical technique is proposed for isolating the pseudo-Rayleigh ( A 0 ) component of the field radiated into the surrounding fluid by a submerged elastic cylindrical shell. The technique is based on the simultaneous use of two fluid–shell interaction models, one based on the Reissner–Mindlin shell theory, and the other on the Kirchhoff–Love shell theory, and is aimed at offering the possibility of analyzing the pseudo-Rayleigh component in its pure form, an approach that has certain rather important advantages over analyzing the component as a part of the overall radiated hydrodynamic pattern. The technique is applied to the analysis of the radiation by two elastic shells with parameters that are common in industry, and the high computational efficiency of the technique is demonstrated.